The October crisis in Chile: readings and interpretations - Araya Leüpin, Eduardo (2022)
This paper is divided into two parts: the first contains a series of discussions presented in the binational seminar for Critical Elections and Social Movements, which took place virtually with professors of the University of Santiago, the Catholic University of Lima and the Catholic University of Valparaiso in July, 2021, organized in collaboration with Professor Carlota Casalino. The second part of the paper addresses the further development of those events, taking place up to the third anniversary of the “social uprising” in Chile, in a radically different political context to the one of October, 2019, which seems to be the closure of a cycle (the constitutional issue yet to be resolved). The paper does not contains a thesis, rather it is a mosaic – certainly incomplete – that connects text revisions and interpretations to personal observations and explaining proposals. It aims to serve as food for thought, not to propose a conclusion, but instead to continue with the passionate exercise of the comparative analysis with our Peruvian colleagues and eventually with others from different latitudes that wish to join us.